ERP post-implementation phase: deployment of the unified theory of acceptance and use of technology (UTAUT) model on user acceptance / Muhammad Rijaluddin Mohamad Zain ... [et al.] - Mohamad Zain, Muhammad Rijaluddin; Tajul Urus, Sharina; -, Thao Trinh; Amirul, Sharifah Milda; Tuan Mat, Tuan Zainun (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
The fourth industrial revolution (IR4.0) has unfurled its wings over all industries, and its positive impact on the modern global economy has already emerged significantly. The need for a real-time, integrated information environment to enhance business operations has motivated companies to employ enterprise resource planning (ERP) systems. Once implemented, the organization's attention has shifted to the most efficient deployment of the ERP post-system usage. User acceptance of the ERP system during the post-implementation phase could determine the overall system's success or failure since the system benefits reside in the exploitation of the integration capabilities. This study aimed to investigate the determinants of user acceptance of post-ERP system usage in Malaysian organizations by adopting the UTAUT model. The five identified factors comprised of performance expectancy, effort expectancy, social influence, facilitating conditions, and behavioural intention. The result suggests that these five factors have a significant positive influence on ERP acceptance among Malaysian ERP users. From a theoretical point of view, the findings open new doors of opportunities by providing new insights into the user's acceptance of ERP in the Malaysian environment. The practical contribution includes recommendations provided to organizations to emphasize the specific factors that increase the effectiveness of the ERP post-implementation phase.